Counselor's Information Service, Volume 33, Number 1, February 1978. A Quarterly Annotated Bibliography of Current Literature on Educational and Vocational Guidance - B'nai B'rith, Washington, DC. Career and Counseling Services; B'nai B'rith, Washington, DC. Career and Counseling Services ([Washington, D.C.]] : Distributed by ERIC Clearinghouse, 1978)
This annotated bibliography of current literature on educational and vocational guidance is divided into the following sections: occupational information; educational, vocational, and personal guidance; guidance administration and procedures; student aids; teacher aids; free or inexpensive guidance material; adult education and the aging; handicapped and rehabilitation counseling; counselor's bookshelf; and periodicals in guidance and related fields. (JLL)
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Administration; Adult Education; Annotated Bibliographies; Career Guidance; Career Planning; Educational Counseling; Occupational Information; Rehabilitation Counseling; Resource Materials; School Counseling; Student Financial Aid; Reference Materials, Bibliographies